Ishod vakuum-potpomognutog dresinga na otvorenom usitnjenom prelomu tibije sa primarnom fiksacijom: Outcome of Vacuum Assisted Dressing in Open Comminuted Tibial Fracture with Primary Fixation - Kumar, Akash; Hosangadi, Adiveppa; Ramesh, Manikya (Scripta Medica, 2023)
Background/Aim: Wound management of the compound open tibia (Gustilo-Anderson grade 2, 3a, 3b) is complicated by a higher infection and the problem of adequate soft tissue coverage is significant. Primary wound closure is not easily advisable in these types of compound open tibial fractures. Early tissue flap or graft procedure might increase the complication rate due to temporary graft rejection and wound infections. The aim of this study was to analyse the duration required for formation of healthy granulation tissue, duration required for making wound fit for skin cover procedure and duration of hospital stay in compound open tibia fracture treated with vacuum assisted closure (VAC). Methods: A prospective interventional study of 22 patients aged 18 to 60 years was done. After assessing the size of the wound, primary bone fixation and wound debridement were carried out as soon as possible and then VAC was applied. Assessment of VAC therapy was based on mean decreases in wound size and “modified Johner and Wruh’s criteria”, used for assessment of the functional outcome of tibial shaft fracture was recorded during each follow-up. Results: Twenty two patients suffered comminuted open fractures of tibia-fibula. Primary fixation of bone were done with vacuum dressing. During follow-up, the good decrease in wound size considering vacuum dressing remedy was once 18.75 ± 18.36 cm2 (p = 0.001). Six patients achieved excellent results according to “modified Johner and Wruh’s criteria” of tibial shaft fracture. Conclusion: This technique effectively reduced wound size, accelerated the formation of healthy granulation tissue of wound with open fracture bone and provided a better functional outcome. The VAC treatment had suggestively increased wound closure rate, decreased morbidity and costs for patients.